2020
DOI: 10.3390/life10030029
|View full text |Cite
|
Sign up to set email alerts
|

Diatom-Derived Polyunsaturated Aldehydes Are Unlikely to Influence the Microbiota Composition of Laboratory-Cultured Diatoms

Abstract: Diatom-derived oxylipins, including polyunsaturated aldehydes (PUA), are considered to have infochemical, allelochemical and bacteriostatic properties, with plausible roles as grazing deterrents and regulators of inter- and intraspecific competition. However, the extent and mechanisms of how PUA influence diatom–bacteria interactions remain unresolved. In this study, impacts on the diversity of the associated bacterial communities (microbiota) of two contrasting Skeletonema marinoi strains (a PUA and a non-PUA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…We did not analyze the diversity of associated microbiota for each experiment. Released PUA could lead to changes in the diversity of the bacterial community for Ncultures and I-cultures, as it has been reported by several authors for coastal bacteria [23], or not, as has been documented by Eastabrook et al [25], for laboratory diatom cultures, but this does not detract from the fact that we found a mutual benefit for growth. We hypothesize that, albeit at nM levels, the PUA released (type and quantity) could contribute to defining a specific organic matter signature of this diatom at each assayed condition.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We did not analyze the diversity of associated microbiota for each experiment. Released PUA could lead to changes in the diversity of the bacterial community for Ncultures and I-cultures, as it has been reported by several authors for coastal bacteria [23], or not, as has been documented by Eastabrook et al [25], for laboratory diatom cultures, but this does not detract from the fact that we found a mutual benefit for growth. We hypothesize that, albeit at nM levels, the PUA released (type and quantity) could contribute to defining a specific organic matter signature of this diatom at each assayed condition.…”
Section: Discussionsupporting
confidence: 83%
“…Some authors showed differential effects of PUA on the growth and metabolism of natural free-living bacterial communities [22,23], and Edwards et al suggested that PUA altered the community structure of particle-associated bacteria suggesting a role in bacterial community succession [24]. Very recently, Eastabrook et al have suggested that PUA is not the main driver of diatom-bacteria interactions in laboratory cultures [25]. Recent publications also consider the significant role of attached bacteria in phosphorus recycling in nature [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the results of Edwards et al [ 58 ], the abundance of free bacteria was almost the same at the end of the experiment, suggesting that PUAs did not influence the bacterial community [ 117 ]. Recently, this latter observation was confirmed, since treatments with heptadienal and octadienal on two strains of S. marinoi , a PUA- and a non-PUA producer, showed no significant differences in bacterial communities between the two cultures [ 118 ]. Overall, these contrasting results reinforce the idea, previously suggested by Paul et al [ 115 ], that PUAs could act in a more complex manner, where additional chemical mediators are also involved.…”
Section: Oxylipins As Cell Signalling Molecules In Diatom Communitmentioning
confidence: 81%